Proposal to reclassify the proteobacterial classes Deltaproteobacteria and Oligoflexia, and the phylum Thermodesulfobacteria into four phyla reflecting major functional capabilities. Issue 11 (5th November 2020) - Waite, David W; Chuvochina, Maria; Pelikan, Claus; Parks, Donovan H; Yilmaz, Pelin; Wagner, Michael; Loy, Alexander; Naganuma, Takeshi; Nakai, Ryosuke; Whitman, William B; Hahn, Martin W; Kuever, Jan; et al.
Abstract : The class Deltaproteobacteria comprises an ecologically and metabolically diverse group of bacteria best known for dissimilatory sulphate reduction and predatory behaviour. Although this lineage is the fourth described class of the phylum Proteobacteria, it rarely affiliates with other proteobacterial classes and is frequently not recovered as a monophyletic unit in phylogenetic analyses. Indeed, one branch of the class Deltaproteobacteria encompassing Bdellovibrio- like predators was recently reclassified into a separate proteobacterial class, the Oligoflexia . Here we systematically explore the phylogeny of taxa currently assigned to these classes using 120 conserved single-copy marker genes as well as rRNA genes. The overwhelming majority of markers reject the inclusion of the classes Deltaproteobacteria and Oligoflexia in the phylum Proteobacteria . Instead, the great majority of currently recognized members of the class Deltaproteobacteria are better classified into four novel phylum-level lineages. We propose the names Desulfobacterota phyl. nov. and Myxococcota phyl. nov. for two of these phyla, based on the oldest validly published names in each lineage, and retain the placeholder name SAR324 for the third phylum pending formal description of type material. Members of the class Oligoflexia represent a separate phylum for which we propose the name Bdellovibrionota phyl. nov. based on priority in the literature and general recognition of the genus Bdellovibrio. Desulfobacterota phyl. nov. includes the taxa previously classified in the phylum Thermodesulfobacteria, and these reclassifications imply that the ability of sulphate reduction was vertically inherited in the Thermodesulfobacteria rather than laterally acquired as previously inferred. Our analysis also indicates the independent acquisition of predatory behaviour in the phyla Myxococcota and Bdellovibrionota, which is consistent with their distinct modes of action. This work represents a stable reclassification of one of the most taxonomically challenging areas of the bacterial tree and provides a robust framework for future ecological and systematic studies.